Content Analysis on Fiscal Sustainability and Government Debt Management in Relation to Legal Regulations - Muhammad Khadziq; Banu Witono (Jurnal Economic Resource, 2026)
This study evaluates the Indonesian government’s fiscal accountability in managing public debt and ensuring fiscal sustainability during 2020–2024. Using a qualitative approach based on document analysis, the research examines official fiscal reports from the Ministry of Finance (State Budget/APBN, Fiscal Risk Statements, and debt disclosures), complemented by audit findings from the Supreme Audit Agency (BPK) and triangulated with verified public statements from national news sources. Data were reduced and coded into two main categories: fiscal sustainability and government debt, and interpreted using principles of public sector accountability and transparency under Law No. 17 of 2003 and Law No. 1 of 2004. Findings indicate fiscal accountability through compliance with debt and deficit rules, progressive post-pandemic deficit reduction, and the publication of debt composition and issuance strategies. However, accountability gaps exist in fiscal risk disclosure, especially regarding contingent liabilities and medium-term debt exposures, which were reported narratively but seldom quantified. Overall, Indonesia’s fiscal practices 2020–2024 show strong procedural accountability but moderate explanatory accountability, suggesting future transparency can be strengthened via deeper analytical disclosure. This study contributes to public sector accounting literature by providing evidence-based insights on fiscal governance post-economic crisis.